New Self-Adaptive Algorithms and Inertial Self-Adaptive Algorithms for the Split Variational Inclusion Problems in Hilbert Space - Chuang, Chih-Sheng; Hong, Chung-Chien (Numerical functional analysis and optimization, 2022)
In the field of convex optimization, numerous problems can be modeled as the split variational inclusion problem. In this paper, we want to give self-adaptive algorithms and inertial self-adaptive algorithms to study the split variational inclusion problems. Next, we propose related convergence theorems under suitable conditions.